Pelatihan Pemanfaatan e-IM3 Creative sebagai Media Pembelajaran Inklusif untuk Guru TK IGTKI Kabupaten Madiun - Sri Anardani; Wasilatul Murtafiah; Rischa Pramudia Trisnani; Hudan Daridiri; Rahma Distya Rosydatul Hapsy (CV. ITTC INDONESIA, 2026)
Inclusive education is a key priority in providing equal educational opportunities for all learners. Interviews and observations involving kindergarten teachers from the IGTKI Association in Madiun Regency revealed that 88% of kindergartens lacked inclusive digital learning media, while only 12% of teachers had previously developed such media. These findings highlight the need to improve teachers' capacity to produce inclusive digital learning resources. To address this issue, training on the e-IM3 Creative application was conducted to enhance teachers' technological literacy and skills in developing inclusive digital learning media. The effectiveness of the training was evaluated using descriptive analysis and a paired sample t-test. The average pre-test scores increased from 1.45–1.55 to 3.30 in the post-test. The paired sample t-test results showed statistically significant improvements across all indicators (p < 0.001), indicating that the training significantly improved teachers' competencies. Feedback survey results also demonstrated positive perceptions of the application: 55% of teachers agreed and 45% strongly agreed that e-IM3 Creative supports classroom learning, while 55% agreed and 40% strongly agreed that it can be effectively used to facilitate learning for children with special educational needs. These findings suggest that e-IM3 Creative is an effective tool for strengthening teachers' competencies and supporting the implementation of inclusive education in early childhood education..